ChemInform Abstract: Fe3O4 Magnetic Nanoparticles (MNPs) as an Efficient Catalyst for Selective Oxidation of Benzylic and Allylic C—H Bonds to Carbonyl Compounds with tert‐Butyl Hydroperoxide. Issue 35 (August 2016) - Zarghani, Monireh; Akhlaghinia, Batool
Abstract: The oxidation reactions are effectively and economically performed under mild conditions.